Two-dimensional core-softened model with water like properties. Study by thermodynamic perturbation theory - Urbic, T. (Condensed Matter Physics, 2013)
Thermodynamic properties of the particles interacting through smooth version of Stell-Hemmer interaction were studied using Wertheim's thermodynamic perturbation theory. The temperature dependence of molar volume, heat capacity, isothermal compressibility and thermal expansion coefficient at constant pressure for different number of bonding sites on particle were evaluated. The model showed water-like anomalies for all evaluated quantities, but thermodynamic perturbation theory does not properly predict dependence of these properties at fixed number of bonding points. Термодинамiчнi властивостi системи частинок, що взаємодiють за допомогою зм’якшеного потенцiалу типу Стелла-Хеммера дослiджено в рамках термодинамiчної теорiї збурень Вертхайма. Розраховано температурну залежнiсть молярного об’єму, теплоємностi, iзотермiчної стисливостi i коефiцiєнта термiчного розширення при сталому тиску для рiзного числа зв’язкiв для заданої частинки. Модель характеризується аномальною поведiнкою властивостей, подiбною до води, але термодинамiчна теорiя збурень незадовiльно описує цi властивостi, якщо число зв’язкiв в розрахунку на частинку є зафiксоване.